Treating Arab Women in Jean Sasson's Princess Sultana's Daughters (Universitas Islam Negeri Sunan Ampel Surabaya, 2018)
Arabian life is depicted through the novel of Jean Sasson's Princess Sultana's Daughters. There are some different treatments accepted by Arab men and women, for example the culture which more honor towards men than women. This case causes the violence and injustice faced by the women. The Arabs often treat them such that by using Islamic teachings as the basis to strengthen their deed. This thesis focuses on analyzing the background of Arabian culture in treating women. This article basically uses Cultural Studies perspective and concept on patriarchy which mainly focuses on Arabian culture making women subordinated. The result shows that the depiction of treating Arab women is based on the cultural tradition.